Road transport system in Southeast Asia; problems and economic solutions - Kaffashi, Sara; Shamsudin, Mad Nasir; Clark, Maynard S.; Ahmad Sidique, Shaufique Fahmi; Radam, Alias (Enviro Research Publishers, 2016)
In Southeast Asian countries (SEA), road transport accounts for the main energy consumption and CO2 emission. Air pollution is a major concern in densely populated cities such as Bangkok, Manila, and Kuala Lumpur. The main objective of this paper is to give insights on trends of transport development, car ownership, and CO2 emissions in Southeast Asia. This study also attempts to review the successful transportation policies around the globe and to introduce the possible instruments that can help reduce air pollution in Southeast Asian countries. Economic instruments to estimate the benefits of a cleaner environment due to new policies are introduced as well. The results of this research could help policy makers consider approaches that could internalize external costs of transportation and maximize the societal welfare.